PENGARUH MODEL KOOPERATIF NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR SISWA SMAN 1 SUNGAI RAYA - Rustina Rustina; Sri Buwono; Ludovicus Maditya Hari Christanto (Universitas Tanjungpura, 2020)
AbstractThis research aims to find out the effects of applying Numbered Head Together (NHT) type of cooperative learning model with classes that apply conventional methods to geography subject. This research is quantitative with experimental research type. The population in this study were all classes of XI IIS which consist of six classes. The sample in this study was class XI IIS 3 as the experimental class by applying Numbered Head Together (NHT) type of cooperative learning model and class XI IIS 2 as the control class with conventional learning method, with the sampling technique using purposive sampling technique. The results of the research in the experimental class obtained an average score of final knowledge test of 82.06 and in the control class an average score of final knowledge test obtained of 75.26. Hypothesis testing conducted was T-Test using the Independent Sample T-Test, with the calculation result obtained is Sig. (2-tailed) of 0,000. In conclusion, there is a difference in student learning outcomes that apply Numbered Head Together (NHT) type of cooperative learning method compared to those using conventional methods in learning geography in class XI IIS SMAN 1 Sungai Raya. Keywords: Learning Outcomes, Numbered Head Together Models